Prediction of the start of next recession using latent factors - Pooi, Ah Hin *; Soo, Huei Ching *; Pan, Wei Yeing (AIP Publishing, 2016)
The data on the binary recession variable and the latent factors extracted from a large set of economic variables are fitted with a multivariate power-normal distribution. A conditional distribution for the recession variable is obtained from the fitted multivariate distribution. The results based on the US economic data show that the 2.5% point of the conditional distribution provides a good indicator for the start of the next recession.